Synthesis, Structural and Magnetic Properties of La0.5Ba0.5CoO2.75+x - Z. Tan; P. Miao; Y. Ishikawa; M. Hagihala; S. Lee; S. Torii; M. Yonemura; T. Kamiyama (PPIKSN-BATAN, 2018)
Hole doping to the Co3+ ion in cobaltite perovskites can significantly modify the electromagnetic properties. We prepared the hole-doped cobaltite perovskites La0.5Ba0.5CoO2.75+x (x = 0.06 and x = 0.15). Neutron powder diffraction and dc-magnetization experiments were performed to investigate the crystal structure and magnetic properties. We found that both of the samples have the cubic crystal structure with space group Pmm in all the measured temperatures. Ferromagnetic transition occurs at 160K in x = 0.15 sample. For x = 0.06, we found the short-range ordered ferromagnetic state and a long-range ordered antiferromagnetic state coexist in low temperature.